Anny Świrszczyńskiej anegdota o przemijaniu. Konceptualizacja upływu czasu w języku poezji - Fert-Cichecka, Elżbieta (Słowo. Studia językoznawcze, 2021)
This article has presented the methods for conceptualization of passage of time in the poetry by a Polish poetess – Anna Świrczyńska. The poetess depicts the process of aging from the individual and personal perspective. She highlights the nontraditional ways of how women’s aging is perceived. The analysis of Świrczyńska’s poetic works has been conducted with linguistic methods based on cognitivism (profiling) and structuralism. In Anna Świrczyńska’s poems, time and passing are one of the elements of life. Thus, apart from negative evaluation, they are subject to positive valorization.